Need for care, adversity exposure and perceived stress in clinical and healthy voice-hearers - Baumeister, David; Ward, Thomas; Garety, Philippa; Jackson, Mike; Morgan, Craig; Charalambides, Monica; Chadwick, Paul; Howes, Oliver; Peters, Emmanuelle (Psychological medicine, 2021)
Objectives - Psychosis, and in particular auditory verbal hallucinations (AVHs), are associated with adversity exposure. However, AVHs also occur in populations with no need for care or distress. - - Aims - This study investigated whether adversity exposure would differentiate clinical and healthy voice-hearers within the context of a ‘three-hit’ model of vulnerability and stress exposure. - - Methods - Samples of 57 clinical and 45 healthy voice-hearers were compared on the three ‘hits’: familial risk; adversity exposure in childhood and in adolescence/adulthood. - - Results - Clinical voice-hearers showed greater familial risk than healthy voice-hearers, with more family members with a history of psychosis, but not with other mental disorders. The two groups did not differ in their exposure to adversity in childhood [sexual and non-sexual, victimisation; discrimination and socio-economic status (SES)]. Contrary to expectations, clinical voice-hearers did not differ from healthy voice-hearers in their exposure to victimisation (sexual/non-sexual) and discrimination in adolescence/adulthood, but reported more cannabis and substance misuse, and lower SES. - - Conclusions - The current study found no evidence that clinical and healthy voice-hearers differ in lifetime victimisation exposure, suggesting victimisation may be linked to the emergence of AVHs generally, rather than need-for-care. Familial risk, substance misuse and lower SES may be additional risk factors involved in the emergence of need-for-care and distress.